Pulmonary embolism in acute lymphoblastic leukemia — An observational study of 1685 patients treated according to the NOPHO ALL2008 protocol. Issue 5 (21st June 2020) - Tuckuviene, Ruta; Bjerg, Cecilie Lundgaard; Jonsson, Olafur Gisli; Langstrom, Satu; Rank, Cecilie Utke; Ranta, Susanna; Saks, Kadri; Trakymiene, Sonata Saulyte; Ruud, Ellen
Abstract: Background: Pulmonary embolism (PE) is a serious complication of acute lymphoblastic leukemia (ALL). We examined the cumulative incidence and clinical presentation of PE in a well‐defined cohort of patients with ALL aged 1‐45 years treated according to the Nordic Society of Pediatric Hematology and Oncology (NOPHO) ALL2008 protocol. Methods: As part of the mandatory toxicity reporting of NOPHO ALL2008, thromboembolism including PE was reported consecutively. The cumulative incidence of first‐time PE was calculated using the Aalen‐Johansen estimator during a 2.5‐year period from ALL diagnosis. We used Fisher's exact test to examine categorical variables and Cox logistic regression to estimate hazard ratios (HRs) for PE. Results: PE was diagnosed in 32 of 1685 patients. The 2.5‐year cumulative incidence of first‐time PE increased with age: 0.43% (95% CI, 0.18‐1.03) in children aged 1‐9 years, 3.28% (95% CI, 1.72‐6.22) in children aged 10‐17 years, and 7.22% (95% CI, 4.61‐11.21) in adults aged 18‐45 years. The majority of PEs, 78% (25/32), occurred during asparaginase treatment. HRs adjusted for age and sex were associated with male sex (HR, 2.4; 95% CI, 1.0‐5.6) and older age (10‐17 years: HR 7.5; 95% CI, 2.5‐22.2), 18‐45 years: HR, 16.5; 95% CI, 6.1‐44.5). In two‐thirds of the patients (63%; 17/27), PE and its treatment had no impact on the administered doses of asparaginase. PE‐associated 30‐day mortality was 9.4% (95% CI, 1.9‐25.0). Conclusions: Awareness of PE is warranted during ALL treatment. Larger multicenter studies are needed to examine predictors of PE in ALL.